Lucas Cranach's Saint Maurice - Ainsworth, Maryan W.; Hindriks, Sandra; Terjanian, Pierre (Metropolitan Museum of Art, 2015)
This Bulletin discusses Lucas Cranach's Saint Maurice and the importance of this saint during the stormy period of the Protestant Reformation in Germany. Anticipating the five-hundredth anniversary of the Reformation, this Bulletin draws on the work of donor Mrs. Eva S. Kollsman and connects this image of Saint Maurice to sculptural relics belonging to Cardinal Albrecht of Brandenburg, the most powerful Roman Catholic prelate at the time. Exhibition: Metropolitan Museum of Art, NYC, USA (April 20 - July 27, 2015)